PERLINDUNGAN FINANSIAL ZAKAT ANAK JALANAN DALAM ALQURAN: Studi Tafsir Tematik Maqâṣidî ibn Sabîl - Andri Nirwana; Muslim Djuned; Muhammad Ikhsan (UIN Siber Syekh Nurjati Cirebon, 2020)
The purpose of this study was to determine the interpreters of the commentators on Ibn Sabil. Ibn Sabil is one of the objects of the distribution of legal alms, in addition to other objects. This research used maudhu’i of tafsir method. The data sources used were primary data and other supporting data relating to the main problem. Based on the data analysis, the conclusion that can be obtained is that Ibn Sabil is said to be entitled to receive zakat if he travels far and runs out of provisions, even though he is a rich man in his native place, and his journey has a goal for beneficence or goodness, whether individuals or groups.